Nevada Levi Delapp, Theophanic "Type-Scenes" in the Pentateuch: Visions of YHWH - Savran, George W. (Journal of Semitic studies, 2020)
George Savran; Nevada Levi Delapp, Theophanic “Type-Scenes” in the Pentateuch: Visions of YHWH, Journal of Semitic Studies, Volume 65, Issue 1, 1 April 2020, P